2019
DOI: 10.1029/2018jg004785
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Spatial Changes in Phytoplankton Community by Water Column Stability and Nutrients in the Southern Yellow Sea

Abstract: The southern Yellow Sea (SYS) shows extensive spatial variations in water masses, particularly YS Warm Current Water (YSWCW) and YS Coastal Current Water in cold and YS Bottom Cold Water (YSBCW) and Changjiang Diluted Water in warm seasons. These hydrographic processes result in significant spatial changes in nutrients, stratification, and turbidity, which may highly regulate phytoplankton distribution in the SYS. Here, we provide high spatial resolution data sets of phytoplankton in the SYS in all seasons dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 55 publications
(155 reference statements)
3
15
0
Order By: Relevance
“…The ECSYS receives a large amount of freshwater and associated macro‐ (N, P, and Si) and micronutrients (e.g., Fe) from Changjiang, resulting in overwhelming dominance of the low‐salinity (≤31), eutrophic CDW in the northern ECS and SYS (Figure ). Such an environment promoted nondiazotrophic phytoplankton (Jiang, Chen, Gao, et al, ) bloom (with high chl‐ a ), but restrained filamentous diazotrophs (Table and Figure ). Table shows DIDs of filamentous diazotrophs were significantly ( p < 0.01) and positively correlated with SSS but negatively with chl‐ a and NO 3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ECSYS receives a large amount of freshwater and associated macro‐ (N, P, and Si) and micronutrients (e.g., Fe) from Changjiang, resulting in overwhelming dominance of the low‐salinity (≤31), eutrophic CDW in the northern ECS and SYS (Figure ). Such an environment promoted nondiazotrophic phytoplankton (Jiang, Chen, Gao, et al, ) bloom (with high chl‐ a ), but restrained filamentous diazotrophs (Table and Figure ). Table shows DIDs of filamentous diazotrophs were significantly ( p < 0.01) and positively correlated with SSS but negatively with chl‐ a and NO 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the offshore and nearshore Kuroshio Branch Currents are found to strongly intrude onto the outer and inner ECS shelf, respectively (Yang et al, ). Taiwan Warm Current (TWC), a mixture between the Taiwan Strait water and the intruded Kuroshio water, flows northward in the ECS and even intrude into the Changjiang Estuary and the southern part of the SYS (Jiang, Chen, Gao, et al, ; Zhou et al, ). Therefore, Kuroshio and its branches strongly intrude into the ECS and SYS (ECSYS), which profoundly influence the physicochemical environment and biogeochemical processes (Chen, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Monthly climatology (Figure ) showed that higher chlorophyll‐a concentration occurred from December to March in the entire BS and the coastal YS, while a maximum in April in the central YS and a July maximum in the Changjiang estuary area, which were in agreement with previous studies (Fu et al, ; Gao & Li, ; Liu & Wang, ; Sun et al, ; Yamaguchi et al, ). These distributions were mainly driven by the interactions of temperature, solar radiation, wind forcing, circulations, and nutients throughout the year (Jiang et al, ). In the BS and coastal YS, Shandong Peninsula coastal front and Yellow Sea coastal front were strongest from January to April (Huang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, due to the strong solar heating and weak wind forcing, shallow MLD took place in summer (Figure d), indicating the existence of a strong thermocline between the shallow mixed surface layer and deeper colder water (Fu et al, ). Stratification was found to be an important factor in controlling the surface phytoplankton biomass and community (Jiang et al, ), since the thermocline barrier prevented the transfer of nutrients from deeper water to the surface layer (Fu et al, ; Wang et al, ; Wei, Yu, et al, ; Xin et al, ), and at the same time, nutrients were depleted in the surface layer after the high biomass in spring, limiting the growth of larger‐sized phytoplankton. Lower chlorophyll‐a concentration and higher percentages of nanoplankton and picoplankton from May to October (Figure and ) were in accordance with previous observations (Fu et al, , ).…”
Section: Discussionmentioning
confidence: 99%
“…The Yellow Sea (YS), located between mainland China and the Korean Peninsula, is a semienclosed marginal sea in the northwest Pacific. Its complex terrain and dynamic circulation field (Chen, 2009; Isobe, 2008; Lie & Cho, 2016) drive the regional physical‐biogeochemical processes (Wei, Yu, et al, 2016) and ecological responses (Fu, Wang, Li, et al, 2009; Jang et al, 2013; Jiang et al, 2019; Liu & Wang, 2013; Liu, Chiang, et al, 2015; Liu, Huang, et al, 2015). As an important component in the western YS, the Jiangsu Shoal (also named the Subei Shoal) and its adjacent area have a unique geographical environment (Figure 1).…”
Section: Introductionmentioning
confidence: 99%